1993
DOI: 10.1007/bf03009771
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine-induced decrease in cerebral blood flow is attenuated by verapamil in rats: a laser Doppler study

Abstract: This study was performed to examine the changes in local cortical blood flow (CoBF) after simultaneous administration of an alpha 2 adrenergic agonist (dexmedetomidine) and a calcium channel antagonist (verapamil) to urethane-anaesthetized rats.Dexmedetomidine given intraperitoneally alone resulted in decreases in mean arterial blood pressure (MABP) (F[27,140] = 3.43; P < 0.01) and CoBF (1:[27,140]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Therefore, the effect of DEX on baseline neuronal activity and CBF was examined. Bolus administration of intravenous DEX (50 μg/kg) induced bradycardia and a transient increase in MABP followed by a gradual decrease in MABP over time by affecting the peripheral nervous system, consistent with earlier reports (Scheinin et al ., ; Vickery & Maze, ; Bari et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the effect of DEX on baseline neuronal activity and CBF was examined. Bolus administration of intravenous DEX (50 μg/kg) induced bradycardia and a transient increase in MABP followed by a gradual decrease in MABP over time by affecting the peripheral nervous system, consistent with earlier reports (Scheinin et al ., ; Vickery & Maze, ; Bari et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…CBF reduction and pial vessel constriction induced by DEX have been well documented for various species. Whereas the cerebral vasoconstriction is mediated by direct agonist binding to α 2 ‐adrenergic receptors on the cerebral vessels (Nakai et al ., ), the degree of vasoconstriction depends on the dose, the delivery method (topical vs. systemic), and anesthetics used prior to DEX administration (Karlsson et al ., ; Zornow et al ., ; Bari et al ., ; Fale et al ., ; McPherson et al ., ; Ishiyama et al ., ; Asano et al ., ; Ohata et al ., ; Iida et al ., ), as well as arterial carbon dioxide tension (Ganjoo et al ., ). For instance, the reductions in CBF and pial arterial diameter in hypocapnic rats were larger than those in normocapnic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found positive antinociceptive interactions between calcium channel blockers and opioids or α 2 -adrenoceptor agonists (Benedek and Szikszay 1984;Del Pozo et al 1987;Horvath et al 1990Horvath et al , 2001Santillán et al 1994;Omote et al 1996;Dogrul et al 2001), however there are only few data on the haemodynamic interactions one would expect to occur after systemic administration of such drug combinations (Van Meel et al 1981;Bloor et al 1989;Bari et al 1993;Méray et al 1994). Van Meel et al (1981) have shown that the α 2 -adrenoceptor mediated vasoconstriction is effectively antagonized by nifedipine or verapamil; these authors attributed this action primarily to the facilitated influx of Ca 2+ .…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, nifedipine attenuates the increase in MAP induced by intravenous dexmedetomidine in isoflurane-anaesthetized dogs (Bloor et al 1989). In an earlier study we found that verapamil did not potentiate the hypotensive effect of dexmedetomidine in rats, but attenuated the reduction of the local cortical blood flow caused by the α 2 -agonist in anaesthetized rats (Bari et al 1993). A study in humans has suggested that low doses of clonidine and nifedipine significantly blunt the decrease in MAP during intubation and decrease the need for fentanyl (Méray et al 1994).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation